IMPLEMENTASI PROGRAM KULIAH KERJA MANDIRI (KKM) DALAM PENGUATAN EDUKASI LINGKUNGAN MELALUI PEMBUATAN TONG SAMPAH ORGANIK DAN NON-ORGANIK DI DESA BONGO NOL, KECAMATAN PAGUYAMAN - Hairul Bariyah; Eka Linda Febriyanti; Nur Sakinah; Fitri Utami Supangkat; Noite Penggu; Yurlian Lamato; Rio Tontoli; Rizal (STKIP Subang, 2026)
Waste management issues in rural areas remain a serious challenge requiring comprehensive and sustainable intervention. Bongo Nol Village, Paguyaman District, Boalemo Regency, faces challenges related to low community awareness regarding organic and non-organic waste management. This Community Service Program (KKM) aims to empower the community by providing waste management infrastructure in the form of organic and non-organic waste bins strategically placed in five hamlets. The implementation method includes field observation, needs analysis, design planning, waste bin production, educational labeling, distribution, and installation at strategic locations with active participation from Youth Organization (Karang Taruna) and local communities. The results demonstrate increased community understanding of the importance of waste sorting from the source and the availability of supporting facilities that enable residents to practice proper waste disposal habits according to waste types. This program serves as concrete evidence of students' contribution to creating a clean, healthy, and sustainable village environment through an education-infrastructure approach based on community participation.